Public opinion towards giving decision: a case study in Alor Gajah Melaka / Atika Rahmad - Rahmad, Atika (Faculty of Business and Management, 2014)
Various research on philanthropy has been conducted by the American and European context, while, research in the context of Asian countries is limited. Therefore, the purpose of this study is to explore on the public opinion among individual Muslim in Masjid Tanah towards their giving decision. There are three (3) factors use in determining the public giving decision. The factors include the public perception on charity, giving and the needy, modalities of giving and socio demographic factors. This study implemented an intercept method as a survey method. A set of questionnaire were distributed around Alor Gajah. Frequency analysis, descriptive analysis, reliability analysis and correlation analysis have been chosen as the method to find the result. The finding indicated that socio demographic factors are the most significant factor that determining the philanthropic donation in the Alor Gajah area as compared to the perception and modalities factors. As for future research, it is suggested that the data gathered should be in a longer period of time because there is a rapid change such as in personal income as well as individual knowledge over time. Since this study is just for 5 months, the result may be questionable in term of their relevancy with the current situation.